1988
DOI: 10.1002/jso.2930380404
|View full text |Cite
|
Sign up to set email alerts
|

Role of tumor‐infiltrating lymphocytes in the host defense mechanism against lung cancer

Abstract: Tumor-infiltrating lymphocytes (TIL) and tumor-associated macrophages (TAM) were recovered from 22 patients with primary lung cancer. The TIL did not exhibit any cytolytic activity against various target cells. The average percentage of TIL recovered was 6.7 +/- 1.3% in patients without recurrence, as compared to 3.6 +/- 0.6% in those with recurrence within 2 years after complete resection of lung cancer (P less than 0.05). The average cytostatic activity of TAM was 38.5 +/- 6.8% in patients without recurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…In several human ma lignancies, the number and antigen expres sion of tumor-infiltrating lymphocytes (TILs) has correlated with the disease status [1][2][3]. In two previous uveal melanoma studies, con flicting results were reported; both studies demonstrated that between 12 and 18% of melanomas had intratumor lymphocytic infil…”
Section: Introductionmentioning
confidence: 49%
“…In several human ma lignancies, the number and antigen expres sion of tumor-infiltrating lymphocytes (TILs) has correlated with the disease status [1][2][3]. In two previous uveal melanoma studies, con flicting results were reported; both studies demonstrated that between 12 and 18% of melanomas had intratumor lymphocytic infil…”
Section: Introductionmentioning
confidence: 49%
“…In humans, local IFN-␥ secretion from activated CD8+ T cells is associated with their in vivo efficacy [5][6][7] and has been explored extensively in a variety of clinical settings [8][9][10]. Although reports indicate that lung cancer cells can be recognized by autologous cytotoxic T cells (CTLs) and might, therefore, be susceptible to specific immunotherapy [11,12], the significance of TILs in lung cancer remains controversial [13][14][15]. Given the fact that patients with NSCLC exhibit high recurrence rates and poor long-term survival, novel tools are of need to identify those patients who may respond to adjunctive therapies, such as immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The response rate was 21.8%. Surprisingly, the responders were limited to renal cell carcinoma (55), melanoma (39), colo-rectal cancer (6), and non-Hodgkin's lymphoma (4). The response rates were, respectively, 29.7, 241, 10.3 and 22.2%.…”
Section: Discussionmentioning
confidence: 93%
“…It is well-known that many human tumors are infiltrated with lymphocytes, but it is not defined well whether autologous tumor-specific cytotoxic lymphocytes exist in the TIL populations or not. On the other hand, many lines of evidence obtained by various in vitro assays suggest that depressed immunological responsiveness of TIL of human tumors [4,5]. Several studies have been reported on the characteristics of IL-2 expanded TIL from human cancer [6][7][8].…”
Section: Introductionmentioning
confidence: 99%